Early‐stage lung adenocarcinoma treated with stereotactic body radiation therapy using a combined deep inspiration breath hold and free breathing technique: case report and literature review. Issue Volume 4:Issues 4(2020) (15th December 2020) - Arbab, Mona; Bartlett, Gregory; DesRosiers, Colleen; Maxim, Peter G; Lautenschlaeger, Tim
Abstract: This case report introduces a new stereotactic body radiation therapy technique using combined deep inspiration breath hold and free breathing to treat lung tumors adjacent to the chest wall. Patients with lung lesions in proximity to the chest wall are at increased risk of developing chest wall toxicity, including pain and rib fracture. We report a case of a 63‐year‐old female former smoker with stage IA1 left lower lobe adenocarcinoma of the lung who was treated with stereotactic body radiation therapy using the deep inspiration breath hold technique and had to receive her last two fractions with free breathing, as she developed a cold and could not hold their breath. This combination resulted in a significant reduction in chest wall 1 cc and maximum dose. Abstract : This case report introduces a new stereotactic body radiation therapy technique using combined deep inspiration breath hold and free breathing to treat lung tumors adjacent to the chest wall with the potential to reduce chest wall 1 cc and maximum dose.